2019
DOI: 10.1186/s13643-019-1086-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding school staff members’ enforcement of school tobacco policies to achieve tobacco-free school: a realist review

Abstract: Background School tobacco policies (STPs) that aim to achieve a tobacco-free environment require consistent enforcement by school staff. However, little is known about why staff choose whether or not to enforce STPs. Therefore, we investigated staff members’ responses to STPs that determine enforcement. Furthermore, we examined how these responses depend on contextual factors at the individual, interpersonal, school, implementation, and national levels. Methods We perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 58 publications
5
29
0
2
Order By: Relevance
“…We identi ed two antagonistic discourses as prominent factors for change commitment: 1) believing that health promotion and smoking prevention is a school role and duty, which legitimizes SFSH versus 2) believing that SFSH violate personal freedom. The rst discourse corresponds with previous research showing that staff enforcement depends on whether staff members believe that STP enforcement is their role and duty 9 , whereas the second discourse has been identi ed as a general barrier to efforts to control environmental tobacco smoke 43 and as a speci c hindering belief for implementing SFSH in the Netherlands. 26 Moreover, the discourses can be said to echo a broader health-political debate concerning which means and models are most appropriate for health promotion and tobacco control.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…We identi ed two antagonistic discourses as prominent factors for change commitment: 1) believing that health promotion and smoking prevention is a school role and duty, which legitimizes SFSH versus 2) believing that SFSH violate personal freedom. The rst discourse corresponds with previous research showing that staff enforcement depends on whether staff members believe that STP enforcement is their role and duty 9 , whereas the second discourse has been identi ed as a general barrier to efforts to control environmental tobacco smoke 43 and as a speci c hindering belief for implementing SFSH in the Netherlands. 26 Moreover, the discourses can be said to echo a broader health-political debate concerning which means and models are most appropriate for health promotion and tobacco control.…”
Section: Discussionsupporting
confidence: 72%
“…This corresponds with the realist review, which contends that staff enforcement depends on whether staff members have con dence to deal with students' negative responses. 9 Additionally, we found that establishing smoking cessation assistance or other help for nicotine-dependent students when implementing SFSH is seen as a necessary action, and this has also been suggested in similar research. 26 Our study shows that, even though SFSH is practiced at two schools, some students smoke during school hours, and it is thus a daily struggle to manage the level of sanctioning and enforcement.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…While the adoption of SFSPs by governments is important ( Rozema et al , 2016 ; Linnansaari et al , 2019 ), such top-down rules only become part of adolescents’ school life if these are consistently enforced by school staff. Consistent enforcement is a crucial requisite for realizing SFSP’s optimum effectiveness on the collective of adolescents ( Wakefield et al , 2000 ; Galanti et al , 2014 ; Schreuders et al , 2017 ), because adolescents may (i) interpret staff’s inconsistent enforcement as a sign that health risks of smoking are not so serious ( Clark et al , 2002 ; Baillie et al , 2007 ), (ii) believe consequences are applied in unfair and biased fashions ( Booth‐Butterfield et al , 2000 ; Gittelsohn et al , 2001 ; Clark et al , 2002 ) and (iii) abuse staff’s leniency in attempts to gradually weaken the rules ( Turner and Gordon, 2004 ).…”
Section: Introductionmentioning
confidence: 99%